Optimizing Students' Metacognitive Abilities through Educational Games Jejak Nusantara in Science Learning - Saputra, I Komang Ardina Ajus; Sudatha, I Gde Wawan (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
Low metacognitive abilities and suboptimal utilization of technology based learning media in science subjects in elementary schools. This condition impacts low motivation, student learning outcomes, and a lack of media variations that suit their needs and learning styles. This study aims to develop and test the effectiveness of the Jejak Nusantara Educational Game Learning Media in improving higher order thinking skills, especially the analysis, evaluation, and creativity aspects of fifth grade students. The method used is research and development (R&D) with the ADDIE model, using a one group pretest posttest design. The trial subjects included three experts (content, design, and learning media) and 30 fifth grade elementary school students. The effectiveness of the media was measured using an A/B test to measure the significance of the increase in pretest and posttest scores. The results showed that the developed media met the criteria of excellent content, design, and technical validity, effectively improving students' metacognitive abilities and learning motivation. The Jejak Nusantara Educational Game is suitable for use as an innovative learning medium that can support the development of higher order thinking skills and technology based learning in elementary schools. The implications of this research indicate that integrating educational game based learning media can be a strategic approach to increasing students' cognitive engagement in the learning process. The Jejak Nusantara game has been shown to encourage students to be more active in planning, monitoring, and evaluating their understanding of science material, which is the core of metacognitive abilities.